2013
DOI: 10.1144/sp386.16
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the provenance and reservoir quality of the Sele Formation sandstones of the UK Central Graben utilizing detrital garnet suites

Abstract: Detrital garnet suites have been demonstrated to be reliable indicators of the mineralogical and lithological characteristics of sediment source areas. This study applies garnet analysis to the Paleocene to Eocene Sele Formation deep-water sandstone units of the central North Sea. These stratigraphic units are economically important as they represent one of the main hydrocarbon reservoir intervals in this mature basin. The routing of turbidity currents into the Central Graben has been demonstrated to be relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…Most applications of heavy mineralogy to lithostratigraphic correlation are subsurface studies and typically examine stratiform hydrocarbon-reservoir sandstones that are sampled in boreholes (Hurst and Morton 1988;Mange-Rajetzky 1995;Morton and Hurst 1995;Morton et al 2010;Kilhams et al 2014).…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Most applications of heavy mineralogy to lithostratigraphic correlation are subsurface studies and typically examine stratiform hydrocarbon-reservoir sandstones that are sampled in boreholes (Hurst and Morton 1988;Mange-Rajetzky 1995;Morton and Hurst 1995;Morton et al 2010;Kilhams et al 2014).…”
Section: Geological Settingmentioning
confidence: 99%
“…There are, however, no outcrop studies of the heavy mineralogy of regionally-developed sand-injection complexes. Because many applications of heavy mineralogy to lithostratigraphy and provenance are concerned with the subsurface, they necessarily examine borehole data (Hurst and Morton 1985;Morton and Hallsworth 1994;Mange-Rajetzky 1995;Morton and Hurst 1995;Kazerouni et al 2011;Kilhams et al 2014;Morton et al 2014). Such studies avoid the potential effects of post-emplacement weathering, but inevitably limit the examination of spatial variations to 1D borehole sections.…”
Section: Introductionmentioning
confidence: 99%
“…garnets or zircons) might reveal their provenance area (e.g. Morton et al 2005;Kilhams et al 2014b;Nielsen et al 2015), if cuttings/cores of nearby sand source areas are available (e.g. well NO 3/7-1 on the Mandal High and wells NO 3/7-3 and Tabita-1 in the Søgne Basin and Tail End Graben, respectively;Verolles 1982;Bonde et al 1994, Fig.…”
Section: Potential Methods For Further Detailed Reservoir Interpretationmentioning
confidence: 99%
“…Work by Morton (1979) and Morton et al (2004) has shown that the chemical composition of garnets differs between the lateral (Gannet and Bittern) and axial (Forties and Cromarty) fans of the Sele Formation, allowing them to be distinguished from each other. Based on the geochemical analyses of several cores and cuttings from wells to the east of Scoter Field, Borella (2011) and Kilhams et al (2014b) showed that garnets in the sandstones had a composition similar to that of the axial fan system, suggesting that the outer boundary of the sidefans was located further towards the west (Fig. 16).…”
Section: Basinwards Extent Of the Side-fansmentioning
confidence: 99%